2008
DOI: 10.1068/p5623
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Eye Movements to Investigate the Picture Superiority Effect in Spatial Memory

Abstract: Spatial memory is usually better for iconic than for verbal material. Our aim was to assess whether such effect is related to the way iconic and verbal targets are viewed when people have to memorize their locations. Eye movements were recorded while participants memorized the locations of images or words. Images received fewer, but longer, gazes than words. Longer gazes on images might reflect greater attention devoted to images due to their higher sensorial distinctiveness and/or generation with images of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Refixations of the same word may actually function as supplementary presentations of the material to be learnt, resulting in the strengthening of that word in memory. Interestingly, Cattaneo et al (2008), who looked at the way people memorized the location of images or words in a display, found that in contrast with the above data, the average duration of single gazes on a particular item was more critical than the number of gazes on that item in predicting the accuracy of its localization at test. More generally, the relationship between eye movements and memory may be explained by the way people focus their attention while scanning scenes, pictures or words, and by the amount of information they extract to optimize their representations in memory (Hollingworth & Henderson, 2002;Kafkas & Montaldi, 2011;Ryan, Leung, Turk-Browne, & Hasher, 2007;Van der Linden et al, 2009).…”
Section: Eye Movements During Encoding Processesmentioning
confidence: 79%
See 1 more Smart Citation
“…Refixations of the same word may actually function as supplementary presentations of the material to be learnt, resulting in the strengthening of that word in memory. Interestingly, Cattaneo et al (2008), who looked at the way people memorized the location of images or words in a display, found that in contrast with the above data, the average duration of single gazes on a particular item was more critical than the number of gazes on that item in predicting the accuracy of its localization at test. More generally, the relationship between eye movements and memory may be explained by the way people focus their attention while scanning scenes, pictures or words, and by the amount of information they extract to optimize their representations in memory (Hollingworth & Henderson, 2002;Kafkas & Montaldi, 2011;Ryan, Leung, Turk-Browne, & Hasher, 2007;Van der Linden et al, 2009).…”
Section: Eye Movements During Encoding Processesmentioning
confidence: 79%
“…Surprisingly, most of the eye-tracking studies that explored people's encoding processes used pictorial material such as visual scenes (e.g., Sharot, Davidson, Carson, & Phelps, 2008;Van der Linde, Rajashekar, Bovik, & Cormack, 2009), pictures (e.g., Kafkas & Montaldi, 2011;Molitor, Ko, Hussey, & Ally, 2014) or faces (e.g., Henderson, Williams, & Falk, 2005). Only very few studies were devoted to the memorization of verbal material (Cattaneo, Rosen, Vecchi, & Pelz, 2008;Geiselman & Bellezza, 1977;Geiselman, Woodward, & Beatty, 1982;Pazzaglia et al, 2014;Tversky, 1974).…”
mentioning
confidence: 99%
“…This study was the first evidence demonstrating the picture superiority effect in both V learners and R learners. Previous studies have found picture superiority effects in normal subjects without classifying their learning styles (3,15,31). In this study, ITM tests were performed 1 h after the recognition tasks.…”
Section: Discussionmentioning
confidence: 95%
“…The picture superiority effect is the concept that pictures are easier to recognize than words (14). Previous studies have demonstrated that subjects could remember pictures better when performing picture and word recognition tasks (3,5,15). However, these studies were designed to recognize stimuli displayed in the short term.…”
mentioning
confidence: 99%
“…However, bibliometric studies offer the advantage of presenting an empirically sound synthesis. Finally, the visual information furnished through scientific mapping is easier to absorb, for longer retention and future research applications (Brady et al , 2008; Cattaneo et al , 2008). Given this series of advantages, we now construct an empirically grounded bibliometric analysis of IMR publications between 1983 and 2019.…”
Section: Literature Reviewmentioning
confidence: 99%